The Influence of Age on Propofol Dosing Requirements During Procedural Sedation in the Emergency Department. (October 2021) - Wells, Maegan E.; Barnes, Ryan M.; Caporossi, Jeffrey; Weant, Kyle A.
Abstract : Propofol is a frequently used agent for procedural sedation in the emergency department (ED). Some have suggested that propofol dosing in this setting should be adjusted in elderly patients; however, limited data exist supporting this recommendation. Additional factors that may contribute to altered propofol dose requirements in this setting have not been thoroughly explored. The objective of this analysis was to ascertain the effect age may have on the propofol dose required during procedural sedation in the ED. This retrospective study was conducted at a Level 1 academic medical center ED and included patients 18 years or older who received propofol for procedural sedation from 2015 to 2017. Those patients who were 18–64 years of age were compared with those 65 years or older. Between the two groups, total and weight-based propofol requirements for sedation, opioid doses, and adverse events were compared. This analysis included 101 procedural sedations. The median induction dose and opioid requirements before or during the procedure were not significantly different between the two groups. Compared with patients 18–64 years of age, those 65 years or older had significantly less total weight-based propofol requirements ( p = 0.024) and required less total propofol for sedation ( p = 0.007). In addition, patients 65 years or older required fewer repeat doses of propofol during the procedure than younger patients ( p = 0.043). The incidence of adverse effects, including respiratory suppression, was not significantly different between the two groups. Patients 65 years or older may have lower weight-based propofol dosing requirements than younger patients. Utilizing a reduced total dose and repeat dosing strategy for propofol in this setting may be indicated. Further investigations are recommended to clarify factors that signal the need for more tailored dosing.